The biological treatment of metalworking fluids: insights into carbon removal mechanisms and integration with biocide toxicity mitigation strategies - Singh, S (2016)
The biological treatment of metalworking fluids (MWFs) is a cost effective alternative to conventional waste disposal processes. While research has proven that this process is capable of treating large volumes of wastes with high organic concentrations, there are uncertainties about the mechanisms by which the treatment occurs, and there are limitations that must be overcome. There is a need to understand the importance of the mechanisms by which carbon (and hence COD) is removed from the wastewater. This will allow for waste practitioners to make better decisions for optimizing the process, and for disposing of waste (i.e sludge) that is generated. The biological treatment process is also susceptible to biocides present within formulations. These compounds either need to be removed before the treatment process, or the bioreactors need to be made more resistant to them to ensure that their presence does not hinder the reactor functioning. This study aims to answer the uncertainties about the carbon removal mechanisms involved in the treatment of oil-containing MWFs. In the first experimental chapter, it is shown that the predominant mechanism of carbon removal is oil/water separation induced by emulsifier degradation, and hence the bioprocess treatment rate is significantly affected by the biodegradability of surfactants and by the presence of cations found naturally in the water that used to prepare the emulsions. The study then provides insights into the potential that coagulation and coalescence has for removing inhibitory components commonly found in MWFs. Coagulation and coalescence is shown to effectively remove biocides with low aqueous solubility (iodopropynyl butylcarbamate) and those that partition themselves into the oil phase (o-phenyl phenate and its sodium salt). Finally, to improve the resistance of reactors to inhibitory compounds, factors influencing the development of fixed-film reactors are investigated. A micro-cosmic system is used to study the both physico-chemical effects and nutritional factors on the development of biofilm reactors. It is shown that biofilm yields can be controlled through pH adjustment, and that these yields are maximized with phosphate stimulation and ammonium limitation. It is then shown that fixed-film reactors are able to treat metalworking fluids even under conditions deemed to be inhibitory. In summary, this project provides insights into further understanding and enhancing the biological treatment of MWFs.